The Genesis and Development of Islamic Economics and Finance - Bilal Ahmad Ganaie (Penerbit Hellow Pustaka, 2025)
The Islamic economic and finance industry has undergone significant transformation, evolving from a nascent sector into a robust global industry since the latter half of the 20th century. This sustained growth has exceeded the expectations of many who were initially skeptical of its viability. During the economic recession of 2008, Islamic economics and finance emerged as an unscathed, ethical, and resonant alternative to the conventional financial systems. As of 2023, the global financial landscape continues to grapple with numerous challenges, including geopolitical tensions, inflation, and excessive debt. Notwithstanding these formidable obstacles, the Islamic Financial Services Industry has persistently demonstrated remarkable growth, with approximately 3.38 trillion U.S. dollars currently engaged in this sector. The Islamic financial system has garnered attention from major international financial institutions, including the International Monetary Fund, the World Bank, and the World Trade Organization. However, despite its notable expansion, some Western scholars, including Timur Kuran, contend that the Islamic economic and financial system is a product of the 20th century and lacks a historical genesis. Kuran has further argued that this system exhibits a sectarian bias, which its founders developed primarily to benefit the Muslim community, thereby neglecting the welfare of other societal segments. Additionally, he posits that the system has been advocated by Abul Ala Mawdudi to support the movement of political Islam. Consequently, this paper seeks to address these critiques and to explore the historical origins and developmental trajectory of the Islamic economic and financial system.